2006
DOI: 10.1074/jbc.m512635200
|View full text |Cite
|
Sign up to set email alerts
|

Hexose-6-phosphate Dehydrogenase Knock-out Mice Lack 11β-Hydroxysteroid Dehydrogenase Type 1-mediated Glucocorticoid Generation

Abstract: The local generation of active glucocorticoid by NADPHdependent, 11␤-hydroxysteroid dehydrogenase type 1 (11␤-HSD1) oxoreductase activity, has emerged as an important factor in regulating hepatic glucose output and visceral adiposity. We have proposed that this NADPH is generated within the endoplasmic reticulum by the enzyme hexose-6-phosphate dehydrogenase. To address this hypothesis, we generated mice with a targeted inactivation of the H6PD gene. These mice were unable to convert 11-dehydrocorticosterone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
144
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(158 citation statements)
references
References 31 publications
14
144
0
Order By: Relevance
“…11 -HSD1 is widely expressed in many tissues (Ricketts et al, 1998) most highly in liver (Tannin et al, 1991) and at lower levels in adipose tissue (Bujalska, et al, 1997, Rask et al, 2001 and in other organs and cells with high GR expression (Whorwood et al, 1991). The activation potential of 11 -HSD1 is dependent on the provision of NADPH co-factor by the co-localised enzyme hexose-6-phosphate dehydrogenase (H6PDH) (Atanasov et al, 2004, Lavery et al, 2006, in the absence of which 11 -HSD1 acts as a dehydrogenase, inactivating cortisol.…”
Section: -Hydroxysteroid Dehydrogenase Typementioning
confidence: 99%
“…11 -HSD1 is widely expressed in many tissues (Ricketts et al, 1998) most highly in liver (Tannin et al, 1991) and at lower levels in adipose tissue (Bujalska, et al, 1997, Rask et al, 2001 and in other organs and cells with high GR expression (Whorwood et al, 1991). The activation potential of 11 -HSD1 is dependent on the provision of NADPH co-factor by the co-localised enzyme hexose-6-phosphate dehydrogenase (H6PDH) (Atanasov et al, 2004, Lavery et al, 2006, in the absence of which 11 -HSD1 acts as a dehydrogenase, inactivating cortisol.…”
Section: -Hydroxysteroid Dehydrogenase Typementioning
confidence: 99%
“…In addition, PKM2 translocation into the nucleus has been described, where it functions as a histone kinase upregulating the expression of c‐Myc and cyclin D1, thereby promoting the Warburg effect and cell cycle progression, respectively (Yang and Lu, 2013). Hexose‐6‐phosphate dehydrogenase (H6PDH), similar to glucose‐6‐phosphate dehydrogenase (G6PD), is important for NADPH production and for the global redox homeostasis (Lavery et al ., 2006). H6PDH is specifically responsible for NADPH generation at the endoplasmic reticulum (ER) lumen, which is also essential for the proper function of ER (Szaraz et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PKM2 translocation into the nucleus leads to the upregulation of c‐Myc and cyclin D1, promoting the Warburg effect and cell cycle progression, respectively. Regardless of H6PD, this is crucial for NADPH production and for the global redox homeostasis (Lavery et al ., 2006; Szaraz et al ., 2010). It has been reported that H6PD knockdown induces autophagy as a survival mechanism up to a threshold of oxidative injury, after which cells undergo apoptosis (Kapuy and Banhegyi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They show increased insulin sensitivity and are protected against metabolic disease (Morton et al, 2001;Morton et al, 2004), show increased angiogenesis following injury (Small et al, 2005) and resist cognitive decline in old age (Yau et al, 2007;Yau et al, 2001). More recently, mice have also been generated which are deficient in hexose-6-phosphate dehydrogenase, the "partner" enzyme to 11β-HSD1 that dictates its enzyme direction through cofactor supply within the endoplasmic reticulum lumen (Lavery et al, 2006). In H6pd -/-mice, the normal reaction direction of 11β-HSD1 is reversed so that it functions exclusively as a dehydrogenase, inactivating glucocorticoids (Lavery et al, 2006).…”
Section: β-Hsd1 Amplifies Glucocorticoid Action In Vivomentioning
confidence: 99%
“…More recently, mice have also been generated which are deficient in hexose-6-phosphate dehydrogenase, the "partner" enzyme to 11β-HSD1 that dictates its enzyme direction through cofactor supply within the endoplasmic reticulum lumen (Lavery et al, 2006). In H6pd -/-mice, the normal reaction direction of 11β-HSD1 is reversed so that it functions exclusively as a dehydrogenase, inactivating glucocorticoids (Lavery et al, 2006). Their phenotype is similar to that of Hsd11b1 -/-mice in that they also show increased insulin sensitivity and alterations in glucose and lipid homeostasis .…”
Section: β-Hsd1 Amplifies Glucocorticoid Action In Vivomentioning
confidence: 99%